A Study On Twenty First Century Cyclones and Their Lifetime Behavior in The Bay of Bengal - Towhiduzzaman, Md.; Al Mohit, Md. Abdul; Rahman, Md. Atikur (Andalasian International Journal of Applied Science, Engineering and Technology, 2022)
Bangladesh is a small disaster prone country in South Asia. The natural hazards of this country increased due to global warming. An informative investigation of cyclone lifetime activity within the Bay of Bengal has been in Analyzed. Cyclone characteristics, mainly lifetime, occurrence were investigated with 21st century cyclone data calibration. The changes of cyclone characteristics were investigated from the Bangladesh Meteorological Department data. The data are observed by their own technology. A statistical and mathematical estimation was performed to investigate the trend and make a best fit of the cyclone behavior line. Major fitted curves are spline, shape-preserve, cubic, quadratic and linear. A significant change of the characteristics has been found due to change of time, which plays a vital role in changing the surge behavior and associated environmental parameters within this area. An increasing trend of occurrence behavior has been found from this study. Significant information comes from this study and the information is about the lifetime of a cyclone. Although the lifetime of cyclones fluctuates due to changes in climate conditions, the lifetime of cyclones will increase in the future. This means that the future cyclone gathers more energy and power. So that, in near future Bangladesh will face more powerful cyclone hazards.